2012
DOI: 10.1002/hep.25591
|View full text |Cite
|
Sign up to set email alerts
|

AP2 adaptor complex mediates bile salt export pump internalization and modulates its hepatocanalicular expression and transport function

Abstract: The bile salt export pump (BSEP) mediates the biliary excretion of bile salts and its dysfunction induces intrahepatic cholestasis. Reduced canalicular expression of BSEP resulting from the promotion of its internalization is one of the causes of this disease state. However, the molecular mechanism underlying BSEP internalization from the canalicular membrane (CM) remains unknown. We have shown previously that 4-phenylbutyrate (4PBA), a drug used for ornithine transcarbamylase deficiency (OTCD), inhibited inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 74 publications
2
55
0
Order By: Relevance
“…Coimmunoprecipitation and subsequent IB analysis showed that 3Â FLAG-BSEP, which is trafficked to the plasma membrane as native BSEP and shows a degradation rate from the cell surface similar to that of native BSEP (Hayashi et al, 2012a), and MRP2 were both ubiquitinated in the same way in 293 cells as in rat hepatocytes, MDCKII cells, and McA-RH7777 cells (Hayashi and Sugiyama, 2009;Hayashi et al, 2012b). Smeared bands around 190 and 210 kDa were detected by anti-Ub antibody in the immunoprecipitates from 293 cells expressing 3Â FLAG-BSEP and MRP2 with anti-FLAG and anti-MRP2 antibodies, respectively (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Coimmunoprecipitation and subsequent IB analysis showed that 3Â FLAG-BSEP, which is trafficked to the plasma membrane as native BSEP and shows a degradation rate from the cell surface similar to that of native BSEP (Hayashi et al, 2012a), and MRP2 were both ubiquitinated in the same way in 293 cells as in rat hepatocytes, MDCKII cells, and McA-RH7777 cells (Hayashi and Sugiyama, 2009;Hayashi et al, 2012b). Smeared bands around 190 and 210 kDa were detected by anti-Ub antibody in the immunoprecipitates from 293 cells expressing 3Â FLAG-BSEP and MRP2 with anti-FLAG and anti-MRP2 antibodies, respectively (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Dronpa-BSEP is trafficked to the CM and undergoes the same regulation for internalization as native BSEP (Hayashi et al, 2012a). In this assay, the internalization of Dronpa-BSEP contributes to the disappearance of fluorescence from the CM after photoactivation of the CM-resident Dronpa-BSEP (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations